A high performance and low cost poly(dibenzothiophene-S, S-dioxide)@TiO2 composite with hydrogen evolution rate up to 51.5 mmol h−1 g−1. Issue 35 (28th August 2020) - Shu, Ge; Wang, Ye; Li, Yuda; Zhang, Song; Jiang, Jia-Xing; Wang, Feng
Abstract : PDBTSO@TiO2 -10 exhibited an extremely high HER of 51.5 mmol h −1 g −1 under visible light illumination. Abstract : The potential application of solar-to-hydrogen conversion requires the realization of high efficiency, low cost, and high stability photocatalyst materials. In this study, a simple homopolymer poly(dibenzothiophene- S, S -dioxide) (PDBTSO) was employed as a compatible component to fabricate TiO2 -containing heterostructures through an in situ polycondensation procedure from cheap commercial materials. The resulting PDBTSO@TiO2 composite with an optimal composition ratio exhibited the highest hydrogen generation rate of 51.5 mmol h −1 g −1, about 1.6 times higher than that of PDBTSO under visible light irradiation. To the best of our knowledge, this is among the top photocatalytic performances reported so far for organic–inorganic heterojunction photocatalysts. Transient absorption spectroscopy revealed that the PDBTSO@TiO2 heterostructure formation could accelerate photo-generated electron transportation from PDBTSO to TiO2, thus increasing the photocatalytic efficiency for hydrogen production. Considering the advantages of high efficiency and low cost, PDBTSO@TiO2 will be a promising active material for commercial photocatalytic applications.